EVALUASI PEMBULUH DARAH PADA ULKUS LABIAL PASCA PEMBERIAN GEL NANOTRANSFERSOME EKSTRAK KULIT JERUK NIPIS (CITRUS AURANTIFOLIA SWINGLE) - Nenny Prasetyaningrum; Sofi Isna Marwati (E-Prodenta Journal of Dentistry, 2023)
Background: Wound healing process has some characteristics, one of them is angiogenesis. Lime peel extract (Citrus aurantifolia Swingle) contains substances that play role in wound healing process. Objectives: This research aims to evaluate the blood vessels in labial ulcer after giving nanotransfersome gel of lime peel (Citrus aurantifolia Swingle) extract. Methods: This research used 32 wistar rats that divided into 8 groups, there are groups that untreated, groups that treated with lime peel gel extract, lime peel nanotransfersome gel extract, and Aloe vera-based herbal medicine respectively for 3 and 7 days. The slide is stained by Hematoxylin Eosin (HE) staining and evaluated using light microscope with 400x magnification by 5 fields. Observation of the number of new blood vessels was indicated by the presence of erythrocytes and endothelial cells which were smaller in size than the main blood vessels. Analysis results showed the significant differences at amount of blood vessels in every groups (p<0.05) and there’s significant correlation at amount of blood vessels in third and seventh days with an increasing correlation coefficient, and lime peel extract nanotransfersome gel group has the highest average. Conclusion: There is a better effect of nanotransfersome gel of lime peel extract (Citrus aurantifolia Swingle) compared to the control group, treatment with Aloe vera-based drugs, and treatment with lime peel extract gel (Citrus aurantifolia Swingle) on the number of blood vessels in the wound healing process labial mucosa of wistar rats on day 3 and 7. Keywords: Wound Healing, Traumatic Ulcer, Lime Peel Extract Nanotransfersome Gel, Blood Vessels